Antarctic Cryptoendolithic Fungal Communities Are Highly Adapted and Dominated by Lecanoromycetes and Dothideomycetes - Claudia Coleine; Jason Stajich; Laura Zucconi; Silvano Onofri; Nuttapon Pombubpa; Eleonora Egidi; Ashley Franks; Pietro Buzzini; Laura Selbmann (Zenodo, 2018)
This is the final paper "Antarctic Cryptoendolithic Fungal Communities Are Highly Adapted and Dominated by Lecanoromycetes and Dothideomycetes" published in Frontiers in Microbiology, Volume 9, 2018,1392 https://www.frontiersin.org/articles/10.3389/fmicb.2018.01392/full Funded by the Italian National Program for Antarctic Researches (PNRA)